BIOMARKER C-REACTIVE PROTEIN (CRP) SEBAGAI PREDIKTOR KOMPLIKASI MAKROVASKULAR PADA PASIEN DIABETES MELITUS TIPE 2 - Abror, Yogi; Rahayu, Ira Gustira; Patria, Cecep (Poltekkes Kemenkes Bandung, 2025)
The prevalence of diabetes mellitus (DM) in Indonesia increased significantly in recent years, with type 2 diabetes mellitus as the most common form. Type 2 DM is strongly associated with macrovascular complications, including coronary heart disease and stroke. Increased fasting blood glucose and C-reactive protein (CRP) levels have been associated with these complications. However, the use of CRP as a predictive biomarker for macrovascular disease in patients with type 2 DM has not been explored. The purpose of this study was to examine the CRP biomarker as a predictor of macrovascular complications in patients with type 2 DM. The findings of this study is to help improve DM management and reduce complications of DM and coronary heart disease. This study was conducted with an Observational Analytic approach to 30 patients type 2 DM selected using a purposive sampling technique. Blood specimens were tested to measure fasting blood glucose and CRP levels, then the results were analyzed using the Saphiro Wilk test followed by the Spearman rank correlation test. The results showed that all participants had fasting blood glucose levels > 200 mg/dL and CRP levels > 5 mg/L. There was a strong positive correlation (R = 0.657) between fasting blood glucose and CRP indicating a relationship between hyperglycemia and blood vessel damage. These findings suggest that CRP may serve as a biomarker to predict macrovascular complications in type 2 DM, thus allowing early detection.